COMPILATIONS AND REPETITIONS IN THE TREATISE ON VERSIFICATION BY OLAVO BILAC AND GUIMARÃES PASSOS - Alckmar Luiz dos Santos (Revista Brasileira de Literatura Comparada, 2024)
This work makes comparisons between António F. de Castilho's Treatise on Portuguese Metrification and Olavo Bilac and Guimarães Passos' Treatise on Versification, locating, analyzing and commenting on the many similarities between them. In the end, an attempt is made to explore a coincidence between the repetition strategy nuanced by some changings used by Brazilian poets, and a writing strategy that is found in the poetic work of one of the two authors.